Pertimbangan Hakim dalam Menetapkan Dispensasi Nikah bagi Anak di Bawah Umur di Pengadilan Agama Bangko - Gunawan Sayuti (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
The age limit determined by the Marriage Law (Article 7 paragraph (1) No. 16 of 2019) is 19 years for men and 19 years for women. Those who wish to marry according to the provisions of the Law must apply for dispensation to the Religious Court. The aim of this research is to determine the judge's considerations in determining marriage dispensation for minors. As well as the factors behind the request for dispensation from marriage for minors. This research method uses a qualitative method which is more specific to field research, namely research whose object is the judge's considerations in determining marriage dispensations. The results of the research show that the judge's considerations in determining the dispensation for child marriage at the Bangko Religious Court, namely, Considerations Based on Nas, Considerations Based on Fiqh Rules, Juridical Considerations (UU), Sociological Considerations, Considerations Based on Ijtihad and Judge's Analysis. The Bangko Religious Court accepts requests for dispensation for the marriage of children who have not reached the specified age for several reasons, including cases of pregnancy outside of marriage, lack of education regarding religion, financial problems, the impact of information channels or social communication facilities, fear of slander, and changes in laws regarding marriage age. In many cases, judges grant this dispensation as a precaution against the possibility of greater harm.